Productivity analysis of timber and fruit tree-based agroforestry practices in Madhupur Sal forest, Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
In developing countries, different agroforestry systems have been promoted as a pathway to increase household incomes and to generate environmental benefits that are well suited to poor farmers. Thus, a study was carried out in the Madhupur Sal forest of Bangladesh to find out the suitable agroforestry systems based on their productivity. Five agroforestry practices namely Akashmoni tree with Ginger and Banana crops, Akashmoni tree with Turmeric and Banana crops, Akashmoni, Acacia Hybrid, Ghoraneem, and Gamar trees with Turmeric crops, Jackfruit and Akashmoni trees with Turmeric and Aroid crops, and Litchi tree with Pineapple, Ginger, Papaya and Banana crops were randomly selected. The non-agroforestry systems (NAFs) for each of the aforesaid practices were also selected.  The study showed that all the selected agroforestry practices were more profitable than their NAFs.  The net profit indicated that Litchi- Pineapple- Ginger- Papaya- Banana based agroforestry practice  was financially more profitable than the other practices while the benefit-cost ratio (BCR) and land  equivalent ratio (LER) were higher (3.66 and 1.76 respectively) in Akashmoni- Ginger- Banana  agroforestry practice followed by Litchi- Pineapple- Ginger- Papaya- Banana, Akashmoni- Turmeric[1]Banana, Akashmoni- Acacia Hybrid- Ghoraneem- Gamar- Turmeric, Jackfruit- Akashmoni[1]Turmeric- Aroid based practices. Even though Litchi- Pineapple- Ginger- Papaya- Banana based agroforestry practice gave higher net profit, the cost required for this practice was much higher. On the other hand, soil pH and content of organic matter, total nitrogen, phosphorus, and potassium in soil of all of the selected agroforestry practices showed higher values than their NAFs. Soil fertility status showed that Akashmoni- Ginger- Banana based agroforestry practice was more fertile as compared to other land uses. The findings revealed that integrated agroforestry systems are more productive than monoculture or NAFs. Both economical and ecological point of view, Akashmoni- Ginger- Banana based agroforestry practice was more suitable than the other practices in the Madhupur Sal forest of Bangladesh.J Bangladesh Agril Univ 18(1): 68–75, 2020https://doi.org/10.5455/JBAU.94743